2013
DOI: 10.1371/journal.pone.0058389
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin Modulates Cytokine/Chemokine Profile in Serum, Improves Bone Marrow Repopulation, and Limits Apoptosis and Autophagy in Ileum after Whole Body Ionizing Irradiation Combined with Skin-Wound Trauma

Abstract: Radiation combined injury (CI) is a radiation injury (RI) combined with other types of injury, which generally leads to greater mortality than RI alone. A spectrum of specific, time-dependent pathophysiological changes is associated with CI. Of these changes, the massive release of pro-inflammatory cytokines, severe hematopoietic and gastrointestinal losses and bacterial sepsis are important treatment targets to improve survival. Ciprofloxacin (CIP) is known to have immunomodulatory effect besides the antimicr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 57 publications
2
50
2
Order By: Relevance
“…It can increase survival by producing effective antiedematous activities, apparently via balancing cytokine levels toward inflammatory attenuation and by reducing neutrophil migration into the lungs. Finally, in contrast to the prosurvival effects of ciprofloxacin in sterile injuries published thus far (1 to 4 h before LPS challenges [9,10]; 2 h after combined irradiation/skin wound trauma [40]), in the present study, ciprofloxacin administration is shown to lead to increased survival even when the drug is first administered at late time points (24 h) following injury onset.…”
Section: Discussioncontrasting
confidence: 93%
“…It can increase survival by producing effective antiedematous activities, apparently via balancing cytokine levels toward inflammatory attenuation and by reducing neutrophil migration into the lungs. Finally, in contrast to the prosurvival effects of ciprofloxacin in sterile injuries published thus far (1 to 4 h before LPS challenges [9,10]; 2 h after combined irradiation/skin wound trauma [40]), in the present study, ciprofloxacin administration is shown to lead to increased survival even when the drug is first administered at late time points (24 h) following injury onset.…”
Section: Discussioncontrasting
confidence: 93%
“…Significant evidence of in vivo and in vitro antiinflammatory activities of fluoroquinolones has been reported previously [38][39][40][41][42]. In particular, with regard to the effects of fluoroquinolones on pro-inflammatory signaling intermediates, it has been reported that norfloxacin and gemifloxacin reduce NFkB expression and activation [43][44][45], and that garenoxacin inhibits Erk1/2 phosphorylation [46].…”
Section: Discussionmentioning
confidence: 98%
“…radiation exposure increase cell death, tissue damage, organ dysfunction, mortality, DNA damages, and severe and rapid loss of hematological components compared to radiation exposure alone. 3 The loss of oral mucosa cells is continuously compensated by proliferation of epithelial cells of the basal layer. 4 Irradiation significantly diminishes the barrier function of the epithelium against different insults (mechanical, chemical and microbial), impairing the balance between cell proliferation and death.…”
Section: Introductionmentioning
confidence: 99%